Extraction and Utilization of Native Cubio Starch (Tropaeolum tuberosum) in the Production of a Frankfurt-Type Sausage - Rey Rodríguez, Javier Francisco; Lizcano Prada, Jennifer; Cuellar Torres, Hasbleidy Giseth (Rev. Téc. Fac. Ing. Univ. Zulia, 2023)
Cubio (Tropaeolum tuberosum) stands as a common tuber across the Andean region, boasting robust nutritional, functional, and rheological traits. This study delved into its potential as a viable replacement for potato starch within an emulsified meat product, particularly the Frankfurt-type sausage. Five formulations were meticulously designed and appraised to pinpoint the two most promising alternatives. Rigorous analyses were conducted on starch physicochemical properties alongside the sausage’s technological aspects, yielding a 1.82% native cubio starch comprising 14.67% amylose and 85.53% amylopectin. Notably, the cubio extract demonstrated a pH of 5.74, while potato registered 6.79, aligning with gelatinization temperatures of 62.6°C and 66.0°C, respectively. The recorded acidity at 0.68±0.05% indicated favorable preservation during storage, attributed to cubio’s inherent antioxidants. Starch colorimetry revealed distinctive gray tones, emphasizing a significant quality metric. Shear force analysis was honed on the most promising formulations. In conclusion, cubio starch emerges as a pragmatic alternative within the meat industry to replace potato starch, albeit with the caveat of heightened production costs due to the starch extraction process.